Diode-pumped Yb, Y:CaF2 laser mode-locked by monolayer graphene. (December 2015) - Zhu, Hongtong; Liu, Jie; Jiang, Shouzhen; Xu, Shicai; Su, Liangbi; Jiang, Dapeng; Qian, Xiaobo; Xu, Jun
Abstract: The large-area and high-quality monolayer graphene saturable absorber with a sandwich structure is prepared by the chemical vapor deposition technique. Using graphene saturable absorber, the mode locking operation of a diode-pumped Yb, Y:CaF2 laser is demonstrated. Without extra negative dispersion elements, 4.8 ps pulses are yielded at 1051 nm. The pulse repetition rate is 60 MHz. Highlights: The monolayer graphene absorber with a sandwich structure was fabricated by CVD. The graphene absorber with high quality was tested and characterized. The Yb, Y:CaF2 laser mode-locked by graphene absorber was realized for the first time.